Pyrophosphate modulates plant stress responses via SUMOylation - Patir, Meliha Gorkem; Andrés González, Zaida; Krebs, Melanie; Fink, Fabian; Drzewicka, Katarzyna; Stankovic-Valentin, Nicolas; Segami, Shoji; Schuck, Sebastian; Büttner, Michael; Hell, Rüdiger; Maeshima, Masayoshi; Melchior, Frauke; et al. (eLife, 2019)
Pyrophosphate (PPi), a byproduct of macromolecule biosynthesis is maintained at low levels by soluble inorganic pyrophosphatases (sPPase) found in all eukaryotes. In plants, H+-pumping pyrophosphatases (H+-PPase) convert the substantial energy present in PPi into an electrochemical gradient. We show here, that both cold- and heat stress sensitivity of fugu5 mutants lacking the major H+-PPase isoform AVP1 is correlated with reduced SUMOylation. In addition, we show that increased PPi concentrations interfere with SUMOylation in yeast and we provide evidence that SUMO activating E1-enzymes are inhibited by micromolar concentrations of PPi in a non-competitive manner. Taken together, our results do not only provide a mechanistic explanation for the beneficial effects of AVP1 overexpression in plants but they also highlight PPi as an important integrator of metabolism and stress tolerance.